A numerical algorithm for zero counting, I: Complexity and accuracy - Cucker, Felipe (2008)
We describe an algorithm to count the number of distinct real zeros of a polynomial (square) system f. The algorithm performs O(log(nDκ(f)))iterations (grid refinements) where n is the number of polynomials (as well as the dimension of the ambient space), D is a bound on the polynomials’ degree, and κ(f) is a condition number for the system. Each iteration uses an exponential number of operations. The algorithm uses finite-precision arithmetic and a major feature of our results is a bound for the precision required to ensure that the returned output is correct which is polynomial in n and D and logarithmic in κ(f). The algorithm parallelizes well in the sense that each iteration can be computed in parallel polynomial time in n, log D and log(κ(f)).